ESPACIALIZAÇÃO DA DENSIDADE DO SOLO NA BACIA HIDROGRÁFICA DO FORMOSO - DA PAZ, Ryan da Silva; CORREA, Helen Caroline Rodrigues; FLORENTIM, Elyson Thiago de Souza; MENEZES, Roniedison da Silva; PANACHUKI, Elói; FALCÃO, Karina dos Santos (ANAIS DO ENIC, 2025)
-